The Ius Constituendum of Regulating Trading in Influence in the Anti Corruption Law - Kevin Daffa Arbi; Muhammad Arief Gunawan Putra Khoifu; Fathia Rahmadini Passa; Aliyah Salsabila Assanti (Journal of Education Technology Information Social Sciences and Health, 2026)
Trading in influence is a corruption offense involving the misuse of real or perceived influence to gain undue advantages. It typically includes three actors: the influence seeker, the intermediary (influence peddler), and the decision-maker. Although Article 18 of UNCAC addresses this as a non-mandatory offense, its regulation is essential for strengthening anti-corruption efforts. Indonesia, despite ratifying UNCAC through Law No. 7 of 2006, has yet to explicitly regulate this practice. This legal research employs statutory, conceptual, and case approaches to examine the gap. In practice, such cases are often prosecuted under alternative provisions that do not fully capture the offense’s essence. Regulatory efforts through the Draft Penal Code and Draft Anti-Corruption Law face obstacles, including evidentiary challenges and fears of overcriminalizing lobbying. Effective regulation must clearly define key elements: the concept of influence, undue advantage, and the parties involved.